Heart rate differences in small sided games in formative basketball - Fernando Gracia; Javier García Rubio; María Cañadas; Sergio Jose Ibáñez (Federación Extremeña de Balonmano; University of Extremadura, 2014)
The aim of this study was to determine and learn the heart rate responses of basketball players in small-sided or modified games, in order to develop a more effective workout plan in the future. The study sample consisted of 19 basketball players from a National Championship Club, 12 of them in the U'14 category and the remaining 7 belonging to the U'16 category. Small-sided games were 3x3 and 4x4 with a duration of 4 minutes and an active break of 3 minutes. Significant differences (p<0.05) were found referring to the relations established between 3x3 without feedback and 3x3 with feedback in vigorous exercise; in 3x3 without feedback and 3x3 with feedback in moderate exercise; in 3x3 and 3x3 with average heart rate; in 4x4 and 4x4 with average heart rate and in 4x4 and 4x4 with average heart rate related to game categories. Keywords: